2018
DOI: 10.3390/rs10071031
|View full text |Cite
|
Sign up to set email alerts
|

Annual Glacier-Wide Mass Balance (2000–2016) of the Interior Tibetan Plateau Reconstructed from MODIS Albedo Products

Abstract: Glaciers in the Tibetan Plateau (TP) play a crucial role in regulating agriculture irrigation, river discharge and the regional/global climate system. However, mass balance records of TP glaciers have remained scarce due to challenging mountainous terrain and harsh weather conditions, which limits our understanding of the influence of melting glaciers on local water resources and responses to climate change. Here, we present and assess an albedo-based method to derive annual mass balance for three glaciers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 69 publications
(108 reference statements)
2
22
0
1
Order By: Relevance
“…Over 2000–17, the contribution of glacier excess meltwater to lake volume change was 20.2%, which should be slightly larger as the Puruogangri Glacier (20% of total glacier area in CC-DC basin) is excluded. Using mass-balance data from 2000 to 2016 from Zhang and others (2018), Qiao and others (2019) suggest that the contribution over 2003–14 is 19.3%.…”
Section: Resultsmentioning
confidence: 99%
“…Over 2000–17, the contribution of glacier excess meltwater to lake volume change was 20.2%, which should be slightly larger as the Puruogangri Glacier (20% of total glacier area in CC-DC basin) is excluded. Using mass-balance data from 2000 to 2016 from Zhang and others (2018), Qiao and others (2019) suggest that the contribution over 2003–14 is 19.3%.…”
Section: Resultsmentioning
confidence: 99%
“…Glacier mass balance has been widely researched based on different methods, e.g., glaciological methods from in situ observation, geodetic methods from multi-temporal DEMs or altimetry data, albedo-based methods from MODIS data, and physical modelbased methods [80]. Data on glacier mass balance based on in situ observations are lacking, due to complex conditions and remote locations with small coverage, and altimetry data only cover some regions of the glacier surface.…”
Section: Mass Budget Analysis 431 Glacial Meltwatermentioning
confidence: 99%
“…Net shortwave radiation is the main driver of the glacier energy balance and largely controls the seasonal and daily variability of glacier melt energy [2][3][4][5][6][7]. Glacier surface albedo directly determines the net shortwave radiation at the surface, thus driving glacier melt, and can therefore be used as a proxy to estimate glacier mass balance [8][9][10]. Previous studies have demonstrated that remote sensing techniques are an efficient means to derive glacier albedo at different spatial and temporal resolutions and can provide an improved understanding of its spatio-temporal evolution over ground observations that are often limited in space and time [11][12][13].…”
Section: Introductionmentioning
confidence: 99%